Hepatic Encephalopathy in Liver Cirrhosis: Precipitating factor and Outcome - Khadka, Dipendra; Khadka, Dipendra; Shrestha, Anil; Bassi, S. D.; Bhandari, Binus (Journal of Nepalgunj Medical College, 2019)
Introduction: Hepatic encephalopathy, one of the major decompensating events of liver cirrhosis manifest as a wide spectrum of neurological or psychiatric abnormalities ranging from subclinical alterations to coma. The main aim of this study was to determine precipitants of hepatic encephalopathy (HE) and their impact on hospital stay and mortality. Methods: A hospital based cross-sectional study carried out in the Department of Medicine, Nepalgunj Medical College, Kohalpur from September 2018 to May 2019. Patients of liver cirrhosis with signs and symptoms of hepatic encephalopathy (HE) were enrolled in the study. Detailed history was taken with patients or patient's visitor regarding precipitating factors. Child Turcotte Pugh (CTP) class was used for assessing liver disease severity and West Haven classification was used for grading of hepatic encephalopathy. Results: Total patients of hepatic encephalopathy studied were 150. Among which, 114 (76%) were male and 36 (24%) were female. Mean age was 45 ± 11years. Common precipitating factors for hepatic encephalopathy identified were constipation 25.3%, Upper gastrointestinal bleed (9.3%), Spontaneous bacterial peritonitis (8%). No identifiable factor was observed in 6.7% cases. Significant relationship was noted with CTP class and grading of Hepatic encephalopathy. Hospital stay was also found longer (≥5 days) among patients having more than one precipitating factor. Conclusions: Early recognition of precipitants and patient education is very crucial in the management of hepatic encephalopathy. Patients having ≥ 2 precipitating factor had longer hospital stay and higher grade of hepatic encephalopathy.